1989
DOI: 10.1177/000456328902600609
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Clinical Evaluation of Three Sensitive Thyrotropin Assays

Abstract: SUMMARY. Three sensitive assays (Behring, Organon and LKB-Pharmacia) for measurement of serum thyrotropin (TSH) were evaluated. All three assays showed good precision, sensitivity, linearity and for practical purposes negligible high dose hook effects. The correlations between the assays were excellent, but due to standardisation and/or matrix effects there were incomplete recoveries in two kits and the kits showed systematic differences of up to 20% in the TSH values obtained.The clinical utility of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Early studies on the Performance of sTSH assays in NTI patients showed normal sTSH concentrations (Spencer, 1986;Faber et al, 1987). By combination of the results of several studies (Alexander et al, 1984;Seth et al, 1984;Kirkegaard et a/., 1985;Semple et al, 1985;Bassett et al, 1986;Krcnning et ul., 1986;Gow et al, 1986;Squire & Gimlette, 1987;Bonte et al, 1989) sTSH measurements in 3421 NTI patients, not selected on severity of illness, could be collected. Only 79 or 2.3% had a suppressed sTSH result, a value to be expected on statistical grounds, because 95% confidence limits were used for the reference population, and consistent with the euthyroid status of these patients (Kaptein et a/., 1981b).…”
Section: Serum Tsh Concentrationmentioning
confidence: 99%
“…Early studies on the Performance of sTSH assays in NTI patients showed normal sTSH concentrations (Spencer, 1986;Faber et al, 1987). By combination of the results of several studies (Alexander et al, 1984;Seth et al, 1984;Kirkegaard et a/., 1985;Semple et al, 1985;Bassett et al, 1986;Krcnning et ul., 1986;Gow et al, 1986;Squire & Gimlette, 1987;Bonte et al, 1989) sTSH measurements in 3421 NTI patients, not selected on severity of illness, could be collected. Only 79 or 2.3% had a suppressed sTSH result, a value to be expected on statistical grounds, because 95% confidence limits were used for the reference population, and consistent with the euthyroid status of these patients (Kaptein et a/., 1981b).…”
Section: Serum Tsh Concentrationmentioning
confidence: 99%